Palliative surgical treatment of patients, suffering proximal tumoral affection of biliary ducts and the jaundice syndrome - Ya. M. Susak; R. Ya. Palytsya; L. Yu. Markulan; O. O. Dyrda (Клінічна хірургія, 2020)
Objective. To compare the efficacy of methods of miniinvasive palliative treatment of malignant hilar strictures with the jaundice syndrome.